2004
DOI: 10.1103/physreve.70.036601
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic enhanced backscattering induced by anisotropic diffusion

Abstract: The enhanced backscattering cone displaying a strong anisotropy from a material with anisotropic diffusion is reported. The constructive interference of the wave is preserved in the helicity preserving polarization channel and completely lost in the nonpreserving one. The internal reflectivity at the interface modifies the width of the backscatter cone. The reflectivity coefficient is measured by angular-resolved transmission. This interface property is found to be isotropic, simplifying the backscatter cone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…We then presented a plausible alternative mechanism for extracting the kinetic energy of the ultra-relativistic pairs: plasma beam instabilities. Despite the extraordinarily dilute nature of this ultra-relativistic pair plasma, we found a variety of plasma instabilities which grow on timescales short in comparison to the inverse-Compton cooling time, the most important of which is the "oblique" instability (Bret et al 2004). Via this instability, these ultra-relativistic pairs lose their kinetic energy by depositing it as heat in the IGM.…”
Section: Introductionmentioning
confidence: 91%
“…We then presented a plausible alternative mechanism for extracting the kinetic energy of the ultra-relativistic pairs: plasma beam instabilities. Despite the extraordinarily dilute nature of this ultra-relativistic pair plasma, we found a variety of plasma instabilities which grow on timescales short in comparison to the inverse-Compton cooling time, the most important of which is the "oblique" instability (Bret et al 2004). Via this instability, these ultra-relativistic pairs lose their kinetic energy by depositing it as heat in the IGM.…”
Section: Introductionmentioning
confidence: 91%
“…Figure 4 shows the angular distribu- Figure 4 is the horizontal cross section of the CBS image through the center of the CBS peak. Limited by the size of the CCD, the right tails are not recorded completely, but they can also be fitted well [12,28].…”
Section: Cbs Experimentsmentioning
confidence: 99%
“…Anisotropic propagation properties of light are studied mainly by transmission measurements [10,12], coherent backscattering (CBS) [11,12,18] and time-resolved techniques [810]. Recently, it has been demonstrated that the anisotropic propagation of light can be controlled by a polarized pump light in a water suspension of anisotropic congruent lithium niobate (CLN) microcrystal particles in the weak localization regime [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning with ground breaking works [9][10][11], main effects were obtained in suspensions or homogeneous powders and ceramics [12]. At the same time-most applications, in particular, biomedical ones [13][14][15][16][17]-deal with optically anisotropic media with pronounced liquid crystal properties.…”
mentioning
confidence: 99%